2009
DOI: 10.1007/s11130-009-0113-4
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Enzymes in Barley Green Biomass

Abstract: Green biomass of young barley plants exhibited statistically significant higher activity of superoxide dismutase (SOD) and catalase (CAT) at sampling I (in the phase of plant development DC 29) compared to the later sampling II (DC 31). Significant effects of varieties, years and interactions of the studied factors on the activity of the studied antioxidants were determined. During the experiment period (2005-2007), the variety Sebastian provided statistically significant higher average SOD activity (486 U.g-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 30 publications
2
14
0
2
Order By: Relevance
“…This is in good accordance with the analysis of barley green mass; there were also only tocopherols determined (Ehrenbergerová et al, 2009).…”
Section: Resultssupporting
confidence: 90%
“…This is in good accordance with the analysis of barley green mass; there were also only tocopherols determined (Ehrenbergerová et al, 2009).…”
Section: Resultssupporting
confidence: 90%
“…Březinová Belcredi et al [16] did not find any significant difference in SOD activity among barley varieties grown in three localities. Ehrenbergerová et al [17] also studied activity in green biomass of varieties/lines of spring barley in the localities Žabčice (518 U.g -1 ) and Kroměříž (363 U.g -1 ), and they determined a significant difference between these localities in the average activity of the studied set.…”
Section:  3 Results and Discussionmentioning
confidence: 99%
“…This is because ROS accumulation and the upregulation of antioxidant enzymes are dependent on plant species, plant genotype, stress severity, stress duration, plant development, and metabolism (Reddy et al 2004). Indeed, a study on barley plants under normal growth conditions showed that SOD and CAT activities were higher at the early developmental stage compared to the late developmental stage (Ehrenbergerová et al 2009). …”
Section: Introductionmentioning
confidence: 99%